A high‐throughput glutathione trapping assay with combined high sensitivity and specificity in high‐resolution mass spectrometry by applying product ion extraction and data‐dependent neutral loss. (31st January 2019) - Wang, Qingping; Liu, Hanlan; Slavsky, Marina; Fitzgerald, Maria; Lu, Chuang; O'Shea, Thomas
Abstract: Reactive metabolites are thought to play a pivotal role in the pathogenesis of some drug‐induced liver injury (DILI) and idiosyncratic adverse drug reactions (IADRs), which is of concern to patient safety and has been a cause of drugs being withdrawn from the market place. To identify drugs with a lower propensity for causing DILI and/or IADRs, high‐throughput assays to capture reactive metabolites are required in pharmaceutical industry for early drug discovery risk assessment. We describe the development of an assay to detect glutathione adducts with combined high sensitivity, enhanced specificity, and rapid data analysis. In this assay, compounds were incubated with human liver microsomes and a mixture of 1:1 of GSH (γ‐GluCysGly): GSX(γ‐GluCysGly‐ 13 C2 15 N) in a 96‐well plate format. UPLC‐UV and LTQ Orbitrap XL were employed to detect GSH‐adducts using the following mass spectrometry setups: (a) selected ion monitoring (SIM) at m/z of 274 ± 3 Da in negative mode with in‐source fragmentation (SCID), which enables simultaneously monitoring two characteristic product ions of m/z 272.0888 (γ‐glutamyl‐dehydroalanyl‐glycine) and 275.0926 (γ‐glutamyl‐dehydroalanyl‐glycine‐ 13 C2 15 N); (b) full scan mode for acquisition of exact mass of glutathione adducts; (c) data‐dependent MS 2 scan through isotopic matching (M:M + 3.00375 = 1:1) for monitoring neutral loss fragments (144 Da from dehydroalanyl‐glycine) and for structural information of glutathione adducts. This approach was qualified using eight compounds known to form GSH conjugates as reported in the literature. The high sensitivity and specificity were demonstrated in identifying unique CysGly adducts in the case of clozapine, diclofenac, and raloxifene and in identifying GSH‐adducts of fragmented parent molecules in the case of amodiaquine and troglitazone. In addition, LC‐UV chromatograms in the presence or absence of GSH/GSX allowed for identification of the rearranged glutathione adducts without aforementioned characteristic fragment ions. Implement of this assay in drug discovery small molecule programs has successfully guided drug design.